Ricardo Carvalho Calero’s Classification of Galician Dialectal Varieties - Dubert-García, Francisco (Madrygal. Revista de Estudios Gallegos, 2021)
This paper aims to analyze Ricardo Carvalho Calero’s dialectological work; more specifically, we will focus on this author’s proposed classification of Galician dialectal varieties. We will begin by presenting his vision of Galician as a unitary language; that is, even though dialectal variation is present, the language does not include dialects, but rather entities that the author called modalities. We will then take a closer look at the development of Carvalho Calero’s classification and its theoretical foundations, as well as provide a description of this proposal. Some of the criticism this proposal has received is also analyzed. The analysis of this latter aspect does not merely have local historiographical value but also reveals important theoretical considerations preliminary to dialectal research. Finally, we conclude that, despite the scarce information that Ricardo Carvalho Calero had available, his organization of the Galician geographical varieties was well-founded and is still deserving of our respect.